PRODUKSI SERBUK EKSTRAK NANGKA DENGAN TEKNIK ENKAPSULASI (Production of Jackfruit Extract Powder Using Encapsulation Technique) - Loebis, Enny Hawani; Junaidi, Lukman (Baristand Industri Banda Aceh, 2015)
Research on production of jackfruit extract using encapsulation technique conducted todiversify jackfruit product to be used as industrial commodity. Treatment on this research was influenceof: anti-caking magnesium oxide (MO), magnesium carbonate (MC), and magnesium silicate (MS), andstorage period (0, 1, 2, and 3 months), on the characteristics of jackfruit powder quality. The resultsshowed encapsulation could be applied to produce jackfruit powder that meets the requirements of SNI01-4320-1996. Based on its quality characteristics, jackfruit powder MO resulted a better qualitycompared to jackfruit powder MC and jackfruit powder MS. Jackfruit powder MO has a qualitycharacteristics: water content 2.04%, pH 4.88, sugar content 84.21%, vitamin C 3.74 mg/100g, totalsoluble solids 97.5%, TPC 120 colonies/g, coliform < 3 MPN/g, and contain no mold and yeast. Storageof jackfruit powder up to 3 months increased water content, pH, and TPC, and contrarily decreased sugarcontent, vitamin C, and total soluble solids. Based on the quality characteristics, jackfruit powder thatwas stored for 3 months still meets the SNI 01-4320-1996 requirements.